1976
DOI: 10.1037/0097-7403.2.4.354
|View full text |Cite
|
Sign up to set email alerts
|

Effects of priming unconditioned stimulus representation in short-term memory on Pavlovian conditioning.

Abstract: A series of four experiments evaluated eyelid conditioning in the rabbit under circumstances in which the unconditioned stimulus (US) could variously be assumed to be prerepresented (primed) in short-term memory at the time of its presentation in pairing with a conditioned stimulus (CS). In both between- and within-subjects comparisons, less conditioning resulted when CS-US pairings were shortly preceded by US presentations than when not. The decremental effect of the pretrial priming US depended upon the simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
57
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 14 publications
5
57
0
Order By: Relevance
“…The preexposure effect observed in the postinjection conditioning paradigm in the present experiments is similar in many ways to the proximal US-preexposure effect recently demonstrated in the forward conditioning of ingestional aversions (Cannon et aI., 1975;Domjan & Best, 1977) and eyeblink responses (Terry, 1976). The magnitude of the interference at moderate preexposure intervals is comparable in the two conditioning procedures (Experiment 3), and in both paradigms the effects of drug pretreatment are similarly determined by the preexposure drug dose and the preexposure interval (Experiments I and 2; Cannon et aI., 1975;Domjan & Best, 1977).…”
Section: Discussionsupporting
confidence: 63%
“…The preexposure effect observed in the postinjection conditioning paradigm in the present experiments is similar in many ways to the proximal US-preexposure effect recently demonstrated in the forward conditioning of ingestional aversions (Cannon et aI., 1975;Domjan & Best, 1977) and eyeblink responses (Terry, 1976). The magnitude of the interference at moderate preexposure intervals is comparable in the two conditioning procedures (Experiment 3), and in both paradigms the effects of drug pretreatment are similarly determined by the preexposure drug dose and the preexposure interval (Experiments I and 2; Cannon et aI., 1975;Domjan & Best, 1977).…”
Section: Discussionsupporting
confidence: 63%
“…That is, the US might serve as a distractor that reduces CS priming (cf. Best et al, 1979;Terry, 1976;Whitlow, 1975). In that scenario, although the US would cancel the effect of the CS, it could itself remain primed and available to influence the next trial.…”
Section: Discussionmentioning
confidence: 99%
“…In an early report using rabbit eyeblink conditioning, Pfautz and Wagner (1976) found that nonreinforced CS presentations shortly before tests of a target CS suppressed responding to the target. Terry (1976) also demonstrated that proximal US presentations can hurt eyeblink conditioning. In flavor aversion learning, a recent exposure to the CS (Best & Gemberling, 1977;Best, Gemberling, & Johnson, 1979), US (e.g., Domjan, 1980), or CS-US pairing (Domjan, 1980) before a single conditioning trial reduces conditioning.…”
mentioning
confidence: 99%
“…A variety of evidence (e.g., Terry, 1976;Whitlow, 1975) suggests that US2-Diff would be more effectively processed than US1-Same. For example, Terry (1976) found that US2 was a more effective reinforcer if it was preceded by a dissimilar US 1 than by a similar US1.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of evidence (e.g., Terry, 1976;Whitlow, 1975) suggests that US2-Diff would be more effectively processed than US1-Same. For example, Terry (1976) found that US2 was a more effective reinforcer if it was preceded by a dissimilar US 1 than by a similar US1. Wagner (e.g., 1978Wagner (e.g., , 1981 suggested that a US2 is less likely to enter into associations if a representation of US2 is already activated in memory, for example, as a result of US1 presentation.…”
Section: Methodsmentioning
confidence: 99%